Vanadium-containing ordered mesoporous silicas: synthesis, characterization and catalytic activity in the hydroxylation of biphenyl - George, J.; Shylesh, S; Singh, AP (Applied Catalysis A - General, 2005)
A series of vanadium-containing ordered mesoporous MCM-41 materials (V-OMS) have been synthesized by direct hydrothermal (VMCM-41) and grafting (V/MCM-41) methods using hexadecyl trimethyl ammonium bromide (HDTMABr) as the structure-directing agent. The physico-chemical properties of the vanadium-containing materials were characterized in detail by ICP-OES, XRD, Fr-IR, N-2 adsorption-desorption, DRUV-VIS, TPR, XPS and SEM techniques. The redox performances of the vanadium-modified mesoporous materials were tested in the hydroxylation of biphenyl using aqueous H2O2 (30 wt.%) as oxidant. For a better exploitation of the catalytic activity, the reaction parameters are optimized in terms of temperature, solvent, oxidant, etc. A comparison between the catalytic activity values of the vanadium-containing mesoporous materials prepared by the two routes shows that vanadium-substituted (V-MCM-41) materials had increased activity and improved selectivity for mono hydroxyl products in the hydroxylation reaction of biphenyl compared to the V/MCM-41 catalysts. The heterogenity of the catalysts was verified by a series of leaching studies. Both the catalysts enhance the leaching of active vanadia species during the reaction; among them, V/MCM-41 shows the least heterogenity. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: biphenyl; heterogenity; MCM-41; Mesoporous molecular sieves; Vanadium

Chemo-, regio- and stereo-selective aerial oxidation of limonene to the endo-1,2-epoxide over Mn(Salen)-sulfonated SBA-15 - Saikia, Lakshi; Srinivas, D.; Ratnasamy, Paul (Applied Catalysis A-General, 2006)
Mn(Salen) complexes immobilized on sulfonic acid-functionalized SBA-15 molecular sieves (SBA-15-pr-SO3-Mn(Salen)) catalyze the Mukaiyama-type oxidation of R-(+)-limonene selectively to the 1,2-epoxide with molecular oxygen at 298 K (Salen = N,N-ethylenebis(salicylidenaminato)). The endo-diastereomer is formed with a diasteromeric excess of 39.8%. This catalyst exhibited higher catalytic activity than ``neat'' Mn(Salen) complexes directly supported on SBA-15 or zeolite-Y. A change in the oxidation state of Mn from +3 in the ``neat'' complex to +2 when immobilized on the sulfonated surface is a probable cause for the observed enhancement of catalytic activity. A part of the Mn complexes was leached out of the solid phase during the reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: aerial oxidation of limonene; catalysis by Mn(Salen) complexes; chemo-; immobilized Mn Schiff base complexes; Mesoporous molecular sieves; Mukaiyama-type oxidation; regio- and stereo-selective epoxidation; sulfonic acid-functionalized SBA-15

Characterization and catalytic activity of cobalt containing MCM-41 prepared by direct hydrothermal, grafting and immobilization methods - Bhoware, Shrikant S.; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2007)
{Cobalt containing hexagonal mesoporous molecular sieves (MCM-41) were prepared by different methods viz., direct hydrothermal synthesis, grafting and immobilization. The calcined material was characterized by various spectroscopic tools such as powder X-ray diffraction (XRD), N-2 adsorption-desorption isotherms, Fourier transformed infra-red (Fr-IR) spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), diffuse reflectance UV-vis and X-ray photoelectron spectroscopy (XPS). The XRD patterns show the highly intense (100) reflection peak in the range 2-3 degrees (2 theta angle), characteristic of mesoporous material. Higher order reflection peaks suggest highly ordered mesoporous structure. N2 adsorption-desorption isotherms are of type IV according to IUPAC classification and the steep rise in the isotherms in the narrow range 3.5-4.5 of relative pressure (P/P-0) is due to the condensation of N-2 gas molecules in the pores (characteristic of mesoporous structure). In FT-IR increase in the intensity of band at 960 cm(-1) with the increase of the cobalt content in Co-MCM-41 samples indicate the incorporation of cobalt ions in the framework of MCM-41. SEM and TEM reveal spherical morphology for the cobalt substituted MCM-41. UV-vis spectra demonstrate the characteristic features of framework and extraframework cobalt in MCM-41. Cobalt is in +2 oxidation state as evidenced from UV-vis and XPS. The catalysts were tested for the side chain oxidation of ethylbenzene using 70 wt.% tert-butyl hydrogen peroxide as an oxidant with and without the use of solvent. Solvents have effect in the catalytic activity and selectivity. In the absence of solvent, substituted cobalt [
Keywords: 2-butanol; cyclohexanone; Mesoporous molecular sieves; MPV reduction

Synthesis, characterization and catalytic performance of Sn-MCM-48 in solvent-free Mukaiyama-type aldol condensation reactions - Taralkar, U. S.; Kalita, Pranjal; Kumar, Rajiv; Joshi, P. N. (Applied Catalysis A-General, 2009)
The influence of various synthesis variables on the physico-chemical properties of mesoporous stannosilicate molecular sieves with MCM-48 structure (Sn-MCM-48) has been investigated. Sn-MCM48 has been used as a new heterogeneous catalyst in solvent-free Mukaiyama-type aldol reactions. Invariably, the beta-hydroxy ester selectivity was found to be 100% irrespective of the conversion level. The product yield was found to increase, to reach a maximum (70%), and then to decrease with the increase in tin content. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Characterization; heterogeneous catalysis; Hydrothermal synthesis; Mesoporous molecular sieves; Mukaiyama-aldol condensation; Sn-MCM-48